Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 86634 by liki last updated on 29/Mar/20

Answered by MJS last updated on 29/Mar/20

∫((cos^2  θ)/(tan θ −1))dθ=       [t=tan θ → dθ=cos^2  θ dt]  =∫(dt/((t−1)(t^2 +1)^2 ))=  =−((t−1)/(4(t^2 +1)))+(1/8)ln (((t−1)^2 )/(t^2 +1)) −(1/2)arctan t =  =(1/4)cos θ (sin θ +cos θ) +(1/4)ln ∣sin θ −cos θ∣ −(θ/2) +C

cos2θtanθ1dθ=[t=tanθdθ=cos2θdt]=dt(t1)(t2+1)2==t14(t2+1)+18ln(t1)2t2+112arctant==14cosθ(sinθ+cosθ)+14lnsinθcosθθ2+C

Commented by liki last updated on 30/Mar/20

Thank you sir

Thankyousir

Terms of Service

Privacy Policy

Contact: info@tinkutara.com